Copy number variations in urine cell-free DNA from bladder neoplasm patients - Cuello Garcia Haider; Qichao Wang; Guangyue Wang; Yinfeng Wang; Yutong Fu; Zhoufan Zhang; Changling Cao; Fengcheng Xue; Haitao Liu; Qian Wang; Jie Zhou; Tingya Jiang; et al. (Molecular and Cellular Probes)
Bladder cancer is a common malignancy, and its diagnosis is based on invasive procedures such as cystoscopy. Genetic aberrations play an important role in the development of many diseases, including bladder cancer. As a result, identifying the genetic basis of a disease can provide useful information for early diagnosis and therapy. Cell-free DNA (cfDNA) offers a non-invasive approach to extract genetic information, which could be valuable for establishing the genetic cause of bladder cancer. In this study, we analyzed copy number variations (CNV) in urine cfDNA from 20 patients, with cystoscopy confirmed bladder cancer, sequenced by next-generation sequencing (NGS) and their CNV examined using the whole genome sequence. Statistical analysis of the carcinoma samples included Wilcoxon and Chi-square tests (p ≤ 0.005). Different patterns in CNV were identified in Chromosomes 1, 2, 3, 5, 6, 8, 9, 10, 11, 12, 17, 19, and 20 with the chromosome cytobands showing significant difference in variation patterns in patient parameters, such as smoking habit, number of tumors, grade of the tumors, and invasiveness. The genes that exhibited distinct CNV in each chromosomal cytoband have been associated with the development and progression of various cancers including bladder cancer indicating the clinical significance of CNVs as a useful tool for disease diagnosis. Therefore, this study demonstrates that by using NGS, CNV in urine cfDNA can provide valuable information on the state of blader cancer which can be further utilized to investigate therapies or early diagnosis.